Pembagian Dividen Tunai terkait Harta Perkawinan jika Terjadi Perceraian - Assyafira, Gisca Nur; Suwono, Surya Harya Nugraha; Wardana, Candika Visnu Candra; Cholis, Arinie Sherlita (Notaire, 2024)
AbstractMarital assets regulated in Law Number 1 of 1974 concerning Marriage, do not regulate in detail the classification of assets that can be used in determining joint marital assets. Apart from that, a husband or wife who owns shares in a company will receive profits in the form of dividends. This type of research is normative juridical legal research, using 3 (three) approaches, namely the statutory approach, conceptual approach and case approach. In this research, the author examines concept regarding shares, cash dividends, marital assets, and divorce. Based on the problem formulation that will be explained: 1) Are cash dividends included in marital assets? 2) What are the legal consequences for the distribution of cash dividends in the event of a divorce? This will raise questions if the shares owned by the husband or wife were obtained before the marriage and dividends were only received during the marriage period. This is a question mark regarding whether these shares are inherited or joint assets in marriage. Then, if there is a divorce, what are the legal consequences for the distribution of joint assets in the form of share dividends? These two problem formulations are the background for the author to carry out this legal research. From this research, the author puts forward a temporary conclusion that cash dividends obtained during the marriage period are joint assets and in the event of a divorce, the distribution of cash dividends can be distributed between husband and wife proportionally according to the applicable laws and regulations. The author’s conclusion is that legislators should be able to form additional regulations that can serve as more specific guidelines for implementing the division of marital assets in the event of a divorce.Keywords: Stocks; Cash Dividends; Joint Property; Divorce. AbstrakHarta benda perkawinan yang diatur pada Undang-Undang Nomor 1 Tahun 1974 tentang Perkawinan, tidak mengatur secara terperinci terkait harta benda dalam menentukan harta bersama perkawinan. Suami maupun istri yang memiliki saham di dalam suatu Perusahaan akan mendapatkan keuntungan berupa dividen. Jenis penelitian ini adalah penelitian hukum yuridis normatif, dengan menggunakan 3 (tiga) pendekatan yakni pendekatan perundang-undangan, pendekatan konseptual, dan pendekatan kasus. Dalam pelitian ini Penulis mengkaji konsep mengenai saham, dividen tunai, harta perkawinan, dan perceraian. Berdasarkan rumusan masalah yang akan dipaparkan adalah: 1) Apakah Dividen Tunai termasuk ke dalam Harta Perkawinan? 2) Apa akibat hukum terhadap pembagian dividen tunai jika terjadi perceraian? Hal tersebut akan menimbulkan pertanyaan jika saham yang dimiliki suami atau istri didapatkan sebelum perkawinan dan dividen baru diterima ketika sudah pada masa perkawinan. Hal inilah yang menjadi tanda tanya bahwa saham tersebut sebagai harta bawaan atau harta bersama dalam perkawinan. Lalu terkait apabila terjadi perceraian, maka bagaimana akibat hukum terhadap pembagian harta bersama berupa dividen tunai. Kedua rumusan masalah tersebut yang melatar belakangi Penulis untuk membuat penelitian hukum ini. Dari penelitian ini, Penulis mengemukakan hasil bahwa dividen tunai yang diperoleh selama masa perkawinan berlangsung merupakan harta bersama yang apabila terjadi perceraian, maka pembagian dividen tunai dapat dibagikan antara suami dan istri secara proporsional menurut peraturan perundang-undangan yang berlaku. Saran dari Penulis, hendaknya Pembentuk Undang-Undang dapat membentuk peraturan tambahan yang dapat menjadi pedoman yang lebih khusus dalam melaksanakan pembagian harta perkawinan jika terjadi perceraian.Kata Kunci: Saham; Dividen Tunai; Harta Perkawinan; Perceraian.